2018
DOI: 10.2196/11632
|View full text |Cite
|
Sign up to set email alerts
|

The QardioArm Blood Pressure App for Self-Measurement in an Obese Population: Validation Study Using the European Society of Hypertension International Protocol Revision 2010

Abstract: BackgroundObesity and high blood pressure (HBP) pose high cardiovascular risks, and they are frequent causes of cardiovascular disease.ObjectiveThe aim of this study was to validate the mobile app QardioArm for high blood pressure monitoring in obese subjects (body mass index ≥30 kg/m2) according to guidelines in the European Society of Hypertension-International Protocol 2 (ESH-IP2).MethodsWe recruited 33 obese subjects and measured their blood pressure using QardioArm (test device) and Omron M3 Intellisense … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…QardioArm in the general population achieved better results in both phases of the protocol for systolic and diastolic BP, especially in part 1 (higher differences in the 3 categories) [28]. Within phase 1, the differences obtained in the systolic BP of renal patients in this study were very similar to those of the general population [28], whereas the differences obtained in the diastolic BP were more similar to the obese population [30]. Phase 2 of this study was almost identical to the 3 previous validations [28-30], with minor differences (1 or 2 individuals).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…QardioArm in the general population achieved better results in both phases of the protocol for systolic and diastolic BP, especially in part 1 (higher differences in the 3 categories) [28]. Within phase 1, the differences obtained in the systolic BP of renal patients in this study were very similar to those of the general population [28], whereas the differences obtained in the diastolic BP were more similar to the obese population [30]. Phase 2 of this study was almost identical to the 3 previous validations [28-30], with minor differences (1 or 2 individuals).…”
Section: Discussionmentioning
confidence: 71%
“…QardioArm has been previously validated for the general population in the first place by our team [28] and later by other authors [29]. In addition, our team validated QardioArm in obese patients [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QardioArm was validated in 2017 [ 36 , 37 ] in the general population. Furthermore, QardioArm has also been validated in a population of obese individuals in 2018 [ 38 ], and recently, in a population of individuals with chronic kidney disease [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, randomized (controlled) trials are necessary to study this assumption. Also, future clinical trials could determine the effect of different electrolytes on blood pressure by patients’ self-assessment of blood pressure with new validated mHealth devices, like a previous study in obese individuals has shown [69].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%